Putusan Pengadilan Tata Usaha Negara Nomor 115/G/2023/PTUN.MDN tentang Pembatalan Sertifikat Hak Milik Perspektif Fiqh Siyasah - Dalimunthe, Ahmad Nawawi; Ramadani, Ramadani (Legal Standing : Jurnal Ilmu Hukum, 2025)
Although land certificates serve as official documents that validate ownership rights, cases of land disputes and violations still often occur. Many individuals face challenges in defending their rights due to the lack of legal protection or the presence of parties who try to harm them. The purpose of this study is to determine how the decision of the state administrative court number 115/G/2023/PTUN.MDN regarding the cancellation of the certificate of ownership rights from the perspective of fiqh siyasah. This study uses a normative legal research method. The results of the study indicate that the PTUN Decision to cancel the Certificate of Ownership Rights (SHM) in the name of Parulian Damanik is contrary to applicable legal procedures and the principle of justice in fiqh siyasah, because the certificate was issued legally by the BPN and has a clear legal basis. Cancellation without evidence of administrative defects causes legal uncertainty, which violates the principle of legal certainty and the government's responsibility to protect individual rights transparently and fairly. This study includes a limited focus on one PTUN case, without expanding the analysis to other similar cases, as well as limited access to supporting documents from related parties. This study is based on the use of the fiqh siyasah approach in analyzing PTUN decisions, which is rarely discussed in the context of modern Indonesian law, and its emphasis on the impact of court decisions on legal uncertainty and justice in land administration. This study contributes to offering a new perspective on the relationship between state law and fiqh siyasah in maintaining individual rights to land.